Isolated deafness as a presenting symptom in granulomatosis with polyangiitis. Issue 3 (16th March 2021) - Kousha, Amy; Reed, Michael; Else, Sara
Abstract : Granulomatosis with polyangiitis (GPA) is a rare small vessel vasculitis commonly affecting the lungs, upper respiratory tract and kidneys. It is an idiopathic condition but likely due to an autoimmune process, resulting in granulomatous lesions and glomerulonephritis. Upper respiratory tract involvement is commonly seen in patients with GPA. Our case is that of an elderly lady (Mrs C) presenting with sudden onset bilateral deafness. She was later found to have extensive lower respiratory tract involvement although she was never particularly symptomatic of this. The presentation suggested a single organ disorder and led to some initial diagnostic uncertainty. Imaging and laboratory investigations eventually led to the diagnosis and she was successfully treated with corticosteroids and rituximab with good response and hearing improvement. This case highlights the importance of early diagnosis in a rapidly progressive disease which undetected can lead to catastrophic end organ damage and disability.